The Total and Active Bacterial Community of the Chlorolichen Cetraria islandica and Its Response to Long-Term Warming in Sub-Arctic Tundra - Klarenberg, Ingeborg J.; Keuschnig, Christoph; Warshan, Denis; Jónsdóttir, Ingibjörg Svala; Vilhelmsson, Oddur (Frontiers in Microbiology, 2020)
Lichens are traditionally defined as a symbiosis between a fungus and a green alga and or a cyanobacterium. This idea has been challenged by the discovery of bacterial communities inhabiting the lichen thalli. These bacteria are thought to contribute to the survival of lichens under extreme and changing environmental conditions. How these changing environmental conditions affect the lichen-associated bacterial community composition remains unclear. We describe the total (rDNA-based) and potentially metabolically active (rRNA-based) bacterial community of the lichen Cetaria islandica and its response to long-term warming using a 20-year warming experiment in an Icelandic sub-Arctic tundra. 16S rRNA and rDNA amplicon sequencing showed that the orders Acetobacterales (of the class Alphaproteobacteria) and Acidobacteriales (of the phylum Acidobacteria) dominated the bacterial community. Numerous ASVs (amplicon sequence variants) taxa could only be detected in the potentially active community but not in the total community. Long-term warming led to increases in relative abundance on class, order and ASV level. Warming altered the relative abundance of ASVs of the most common bacterial genera, such as Granulicella and Endobacter. The potentially metabolically active bacterial community was also more responsive to warming than the total community. Our results suggest that the bacterial community of the lichen C. islandica is dominated by acidophilic taxa and harbors disproportionally active rare taxa. We also show for the first time that climate warming can lead to shifts in lichen-associated bacterial community composition.